Glutathione in Plant Growth, Development, and Stress Tolerance 2017
DOI: 10.1007/978-3-319-66682-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Plant Glutathione Peroxidases: Antioxidant Enzymes in Plant Stress Responses and Tolerance

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. The publisher, the authors and the editors are safe to assume that the advice and information in this book are believed to be true and accurate at the date of publication. Neither the publisher nor the authors or the editors give a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…Several studies support that glutathione plays an essential role in Fe-deficiency tolerance and NO-mediated Fe-deficiency signalling in plants (Ramírez et al, 2008(Ramírez et al, , 2009Koen et al, 2012;Shanmugam et al, 2012Shanmugam et al, , 2015. Data are also in line with previous studies on GSH in different abiotic stresses in other plant species (Chen et al, 2010(Chen et al, , 2017Hussain et al, 2016;Akram et al, 2017;Bela et al, 2017;Cao et al, 2017).…”
Section: Effects Of Foliar Fertilisation With Gsh Alone or Supplementsupporting
confidence: 86%
“…Several studies support that glutathione plays an essential role in Fe-deficiency tolerance and NO-mediated Fe-deficiency signalling in plants (Ramírez et al, 2008(Ramírez et al, , 2009Koen et al, 2012;Shanmugam et al, 2012Shanmugam et al, , 2015. Data are also in line with previous studies on GSH in different abiotic stresses in other plant species (Chen et al, 2010(Chen et al, , 2017Hussain et al, 2016;Akram et al, 2017;Bela et al, 2017;Cao et al, 2017).…”
Section: Effects Of Foliar Fertilisation With Gsh Alone or Supplementsupporting
confidence: 86%
“…During stressed conditions, the enzyme glutathione peroxidase (GPX) uses GSH as a reducing agent to remove excess H 2 O 2 induced by abiotic stresses, into the oxidized glutathione, GSSG. In defense against the overproduced ROS during stresses, the enzyme glutathione reductase (GR) then reduces GSSG back into GSH, further maintaining the GSH/GSSG homeostasis ( Cao et al, 2017 ; Bela et al, 2017b ). Evidently, various studies showed up-regulation of genes encoding GPX and a significant increase in GR activities in plants that were subjected to abiotic stresses such as metal toxicity, salinity, drought, and temperature extremities ( Nahar et al, 2015 ; Ding et al, 2016 ; Hussain et al, 2016 ; Li et al, 2021 ).…”
Section: Glutathionementioning
confidence: 99%
“…Generally, the uptake of HMs from the contaminated soil by the plants will result in an overproduction of ROS, causing oxidative stress and damage to the plants. In response, GSH, of the antioxidant defense system, participates in the detoxification of toxic HMs through three possible pathways which include, direct scavenging of ROS in the AsA-GSH cycle, HM chelation through the synthesis of phytochelatins (PCs), and conjugation of HMs catalyzed by glutathione S-transferase (GST; Bela et al, 2017b ; Cao et al, 2017 ).…”
Section: Roles Of Exogenous Gsh In Stressed Plantsmentioning
confidence: 99%
“…The results could be attributed to the fact that Cu/Zn-SOD mainly functions as a ROS scavenger in the cytoplast and only scavenges ROS a little in chloroplasts [44]. GPX catalyzes the reduction of H 2 O 2 , organic hydroperoxide, and lipid peroxides using glutathione (GSH), thioredoxin (TRX) and/or other reducing equivalents and is generally considered to be the main line of enzymatic defense against oxidative membrane damage [45][46][47]. GPX has been proven to function as both a redox transducer and an ROS scavenger in abscisic acid and drought stress response in Arabidopsis [48].…”
Section: Discussionmentioning
confidence: 99%